Application of a Rod USB Digital Microscope for Pelvic Examination Demonstration for Fourth Year Medical Students: An assessor-blinded randomized trial - Patsira Warinsiriruk; Yada Tingthanatikul; Anusorn Adirekkittikun; Jittima Manonai Bartlett (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To evaluate the students' satisfaction of the fourth year medical students learning the pelvic examination and the benefits of the rod USB digital microscope compared with the traditional method.Materials and Methods: The fourth year medical students were recruited after commencing gynecologic rotation and were randomly assigned to receive the traditional method and the rod USB digital microscope assisted method on pelvic examination demonstration. There was only one trainer performing all demonstration session and all participants were not informed to which group they were assigned. The validated 5-question students' satisfaction questionnaire was used to evaluate the participants' satisfaction by assessor-blinded, randomized trial and the validated 5-question rod USB digital microscope questionnaire was used to evaluate its benefits. The primary outcome was students' satisfaction of pelvic examination learning with the rod USB digital microscope.Results: There were 35 students in the study group (21 female, 14 male, aged 22.14 ± 0.36 years) and 35 students in the control group (25 female, 10 male, aged 22.12 ± 0.33 years). The overall satisfaction score of the study group was significantly higher than that of the control group (4.88 ± 0.12 vs 3.69 ± 0.69) (p < 0.001). Regarding the benefits of the instrument, the overall mean score was 4.75 ± 0.24, and the highest score was the use for medical student teaching (mean score 4.97 ± 0.17). Conclusion: The rod USB digital microscope could be applied to pelvic examination demonstration with high satisfaction of the fourth year medical students.